Life ascending : the ten great inventions of evolution - Lane, Nick, 1967- (W.W. Norton, 2010)
Nick Lane expertly reconstructs the history of life by describing the ten greatest inventions of evolution (including DNA, photosynthesis, sex, and sight), based on their historical impact, role in organisms today, and relevance to current controversies.